Determination of 1, 5‒anhydro‒glucitol–carrier protein conjugates by matrix‒assisted laser desorption/ionization tof mass spectrometry and antibody formation. Issue 3 (2000) - Xuan Xuan, Li-Jiang Li-Jiang; Tanaka Tanaka, Hiroyuki Hiroyuki; Morimoto Morimoto, Satoshi Satoshi; Shoyama Shoyama, Yukihiro Yukihiro; Akanuma Akanuma, Hiroshi Hiroshi; Muraoka Muraoka, Keiji Keiji
Abstract : In order to prepare the monoclonal antibody against 1, 5-anhydro-glucitol (1 ), it was conjugated with bovine serum albumin (BSA), human serum albumin (HSA) or chicken lysozyme (CL) using succinate or β -alanine succinate as a spacer to produce individual antigen conjugates. The number of hapten contained in each antigen conjugate was determined by matrix-assisted laser desorption/ionization tof mass (MALDI-tof-MS) spectrometry. The formation of monoclonal antibody (MAb) was also discussed.